Longitudinal assessment of thyroid function in dogs with hypoadrenocorticism: Clinical outcomes and prevalence of autoantibodies - Nadja S. Sieber‐Ruckstuhl; Barbara Riond; Federico Fracassi; Claudia Kuemmerle‐Fraune; Solène Meunier; Regina Hofmann‐Lehmann; Claudia E. Reusch; Claudia Mueller; Natalie Hofer‐Inteeworn; Felicitas S. Boretti (Journal of Veterinary Internal Medicine)
Abstract Background Knowledge about primary hypoadrenocorticism coexisting with immune‐mediated thyroiditis (Schmidt's syndrome) in dogs is limited. Objective To evaluate thyroid function in dogs with naturally occurring hypoadrenocorticism before and during treatment. Animals Sixty‐six client‐owned dogs. Methods Measurement of canine thyroid stimulating hormone (cTSH), total thyroxine (T4), free thyroxine, and autoantibodies against thyroglobulin, T4, and total triiodothyronine. Results Thirty‐eight dogs were assessed before and 28 during treatment. Follow‐up data were available for 24/38 and 17/28 dogs, with median follow‐up duration of 3.8 years (range, <1.0‐8.8 years) and 4 years (range, 1.1 weeks to 10.5 years), respectively. Canine thyroid stimulating hormone was above the reference range at the time of diagnosis of hypoadrenocorticism in 10 of 38 dogs but decreased into the reference range in 7 for which follow‐up data was available. Hypothyroidism was confirmed in 5 dogs at a median age of 11 years (range, 7‐15 years). In 4 dogs, the condition was diagnosed after a median treatment duration of 5.75 years (range, 2.6‐10 years), while in 1 dog, the diagnosis was made concurrently. One dog had detectable thyroid autoantibodies. Conclusions and Clinical Relevance Hypothyroidism occurs as a rare concurrent condition in dogs with hypoadrenocorticism, potentially at any phase of treatment. Close monitoring of cTSH levels in these dogs could be beneficial, as early changes might indicate the onset of hypothyroidism. The low prevalence of detectable thyroid autoantibodies suggests that nonimmune mechanisms might contribute to thyroid dysfunction.